The Influence of Talent Management and Human Resource Audit on Employee Performance at PT. Bintani Megahindah in Taliabu, North Maluku - Eva Natasya La Ade; Rukhayati; Rahmiwati Habibu (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
This study aims to analyze the influence of talent management and human resource audits on employee performance. The research method used is quantitative with an associative approach. The population in this study was all employees, with a saturated sampling method used to select the entire population. Data collection techniques included questionnaires, observation, and documentation. Data analysis used multiple linear regression with IBM SPSS Statistics.The results indicate that talent management has a partial positive but insignificant effect on employee performance, with a significance value of 0.535 (>0.05). Meanwhile, human resource audits have a positive and significant effect on employee performance, with a significance value of 0.040 (<0.05). Simultaneously, talent management and human resource audits have a significant effect on employee performance, with a significance value of 0.003 (<0.05). The coefficient of determination (R²) of 0.217 indicates that talent management and human resource audits explain 21.7% of the variation in employee performance, while the remaining 78.3% is influenced by other variables outside the study.